Accumulation of succinate controls activation of adipose tissue thermogenesis - Mills, Evanna L.; Pierce, Kerry A.; Jedrychowski, Mark P.; Garrity, Ryan; Winther, Sally; Vidoni, Sara; Yoneshiro, Takeshi; Spinelli, Jessica B.; Lu, Gina Z.; Kazak, Lawrence; Banks, Alexander S.; Haigis, Marcia C.; et al. (Nature (London), 2018)
Thermogenesis by brown and beige adipose tissue, which requires activation by external stimuli, can counter metabolic disease 1 . Thermogenic respiration is initiated by adipocyte lipolysis through cyclic AMP–protein kinase A signalling; this pathway has been subject to longstanding clinical investigation 2 – 4 . Here we apply a comparative metabolomics approach and identify an independent metabolic pathway that controls acute activation of adipose tissue thermogenesis in vivo. We show that substantial and selective accumulation of the tricarboxylic acid cycle intermediate succinate is a metabolic signature of adipose tissue thermogenesis upon activation by exposure to cold. Succinate accumulation occurs independently of adrenergic signalling, and is sufficient to elevate thermogenic respiration in brown adipocytes. Selective accumulation of succinate may be driven by a capacity of brown adipocytes to sequester elevated circulating succinate. Furthermore, brown adipose tissue thermogenesis can be initiated by systemic administration of succinate in mice. Succinate from the extracellular milieu is rapidly metabolized by brown adipocytes, and its oxidation by succinate dehydrogenase is required for activation of thermogenesis. We identify a mechanism whereby succinate dehydrogenase-mediated oxidation of succinate initiates production of reactive oxygen species, and drives thermogenic respiration, whereas inhibition of succinate dehydrogenase supresses thermogenesis. Finally, we show that pharmacological elevation of circulating succinate drives UCP1-dependent thermogenesis by brown adipose tissue in vivo, which stimulates robust protection against diet-induced obesity and improves glucose tolerance. These findings reveal an unexpected mechanism for control of thermogenesis, using succinate as a systemically-derived thermogenic molecule. A comparative metabolomics approach is used to identify succinate as a key activator of thermogenesis in brown adipose tissue.